A Development of Learning Activity based on Problem-Based Learning with Online Media to Promote Collaborative Problem-Solving Competency of Grade 11 students on Topic of Solutions - Buamul, Juthamat; Sawangboon, Tatsirin (Ratchaphruek Journal, 2023)
The objectives of this research were to 1) develop learning activities based on problem-based learning (PBL) with online media to meet the required efficiency 75/75, 2) compare mean scores of collaborative problem-solving competency with high-level criteria and 3) study the satisfaction of the students who leaned with learning activities based on PBL with online media. The sample of this research was 39 students in grade 11 in the second semester of 2021 academic year at Phadungnaree School. The sample was recruited by a cluster random sampling. The research instruments were 1) the lesson plan on PBL with online media on the topic “Solutions”, 2) the achievement test, 3) the collaborative problem-solving competency test, and 4) the satisfaction assessment inventory. The data analysis in this study consisted of percentage, mean, standard deviation and t-test one sample. The results of this research indicated that 1) the learning activities based on PBL with online media had an effective (E1/E2) of 79.54/77.98, 2) the students who leaned with learning activities based on PBL with online media had collaborative problem-solving competency at high level ( = 19.87, S.D. = 2.23) with a statistical significance level of .05 and 3) the students who leaned with learning activities based on PBL with online media had the satisfaction in learning activities at high level ( = 3.71, S.D. = 0.77).